2014
DOI: 10.1158/1055-9965.epi-13-0870
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Hepatocellular Carcinoma Using a Prospectively Developed and Validated Model Based on Serological Biomarkers

Abstract: Background: Hepatocellular carcinoma is a common complication of chronic liver disease (CLD), and is conventionally diagnosed by radiological means. We aimed to build a statistical model that could determine the risk of hepatocellular carcinoma in individual patients with CLD using objective measures, particularly serological tumor markers.Methods: A total of 670 patients with either CLD alone or hepatocellular carcinoma were recruited from a single UK center into a case-control study. Sera were collected pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
275
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(287 citation statements)
references
References 51 publications
3
275
2
7
Order By: Relevance
“…Other than AFP, the Lens culinaris agglutinin-reactive glycoform of AFP (AFP-L3), des-γ-carboxyprothrombin, Golgi protein 73 and osteopontin have been evaluated in the screening population [95,96]. On the whole, these tumor markers have modest performance but may pick up a proportion of AFP-negative HCCs.…”
Section: How May the Knowledge Of Hcc Risk Be Translated Into Clinicamentioning
confidence: 99%
“…Other than AFP, the Lens culinaris agglutinin-reactive glycoform of AFP (AFP-L3), des-γ-carboxyprothrombin, Golgi protein 73 and osteopontin have been evaluated in the screening population [95,96]. On the whole, these tumor markers have modest performance but may pick up a proportion of AFP-negative HCCs.…”
Section: How May the Knowledge Of Hcc Risk Be Translated Into Clinicamentioning
confidence: 99%
“…The incorporation of clinical variables like age and gender into models based on a combination of biomarkers for HCC detection further improve the predictive performance of these models [39] . A model using a combination of age, gender, AFP, AFP-L3 and DCP estimates the probability to suffer from HCC in an individual patient with chronic liver disease with a sensitivity of 86% for HCC in BCLC stage 0 or A and a sensitivity of 94% for later tumor stages [40] . The diagnostic performance of novel circulating biomarkers and scores is summarized in Table 2.…”
Section: Role Of Biomarkers In Surveillance and Diagnosismentioning
confidence: 99%
“…Although tumor marker levels are not included in the diagnostic criteria for HCC or in the screening recommendations in the guidelines of the American Association for the Study of Liver Diseases or the European Association for the Study of the Liver [15,16], they provide valuable supportive information for diagnosing HCC. Furthermore, a recent study found that the combination of these three tumor markers was useful for diagnosing HCC; this combination had very high sensitivity and specificity for diagnosing HCC without the use of imaging studies [17].…”
Section: Introductionmentioning
confidence: 99%